2019
DOI: 10.4293/jsls.2019.00018
|View full text |Cite
|
Sign up to set email alerts
|

Vaginal Cuff Dehiscence After Endometriosis Surgery

Abstract: Background and Objectives: Laparoscopic hysterectomy is one of the surgical treatment options for endometriosis. A rare complication of this surgical procedure is vaginal cuff dehiscence, with an incidence of 0.03% to 0.30%. Sexual intercourse may be the main triggering event. It is unclear if patients with endometriosis are more prone to develop vaginal cuff dehiscence than other women undergoing laparoscopic hysterectomy. Methods: We present the cases of women aged 35… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 11 publications
0
10
0
Order By: Relevance
“…coagulation instead of cutting mode for vaginal incision [ 111 ]), transvaginal closure of the vault, use of single instead of continuous stiches, postoperative infection and supravaginal hematoma [ 106 , 108 ]. Patient-related risks for developing VCD are: premenopausal status, smoking habit, and preexistent endometriosis [ 103 , 105 113 ]. No differences in the frequency of VCD were noted in relation to the use of barbed versus non-barbed suture (polyglactin 910) [ 114 ] or single-layer versus double-layer barbed suture [ 108 , 115 ], with the exception of RALS, where the use of barbed sutures was associated with better healing and fewer separations of the vaginal cuff [ 108 , 116 ].…”
Section: Methodsmentioning
confidence: 99%
“…coagulation instead of cutting mode for vaginal incision [ 111 ]), transvaginal closure of the vault, use of single instead of continuous stiches, postoperative infection and supravaginal hematoma [ 106 , 108 ]. Patient-related risks for developing VCD are: premenopausal status, smoking habit, and preexistent endometriosis [ 103 , 105 113 ]. No differences in the frequency of VCD were noted in relation to the use of barbed versus non-barbed suture (polyglactin 910) [ 114 ] or single-layer versus double-layer barbed suture [ 108 , 115 ], with the exception of RALS, where the use of barbed sutures was associated with better healing and fewer separations of the vaginal cuff [ 108 , 116 ].…”
Section: Methodsmentioning
confidence: 99%
“…We categorized the risk factors for VCD(E) into three groups: external force on the vaginal cuff, patient factors (physiological or pathological), and TH-related factors. Vaginal trauma during coitus is the most common trigger of VCD(E) ( 1 , 4 ). Transvaginal procedures can also lead to VCD(E), including transvaginal ultrasonography ( 7 ) and intracavitary brachytherapy ( 8 ).…”
Section: Discussionmentioning
confidence: 99%
“…It mainly involves hemostasis (hemostatic and local compression), activity restriction, and prophylactic antibiotics. Zoë Boersen et al ( 1 ) reported two cases that were successfully managed conservatively. Notably, if the patient’s condition worsens, surgical intervention should be considered.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The bladder and rectum may require further dissection to allow at least 1 cm of full-thickness bite during closure [4,5]. Similar to the management of initial cuff closure, there is no one recommended way to close the cuff after a dehiscence has occurred [1,2,[39][40][41]. Some authors favor monofilament sutures for the theoretical advantage of reducing infection [42,48,49].…”
Section: Managementmentioning
confidence: 99%